A systems perspective on placental amino acid transport. (7th September 2018) - Cleal, Jane K.; Lofthouse, Emma M.; Sengers, Bram G.; Lewis, Rohan M.
Abstract : Abstract: Placental amino acid transfer is a complex process that is essential for fetal development. Impaired amino acid transfer causes fetal growth restriction, which may have lifelong health consequences. Transepithelial transfer of amino acids across the placental syncytiotrophoblast requires accumulative, exchange and facilitated transporters on the apical and basal membranes to work in concert. However, transporters alone do not determine amino acid transfer and factors that affect substrate availability, such as blood flow and metabolism, may also become rate‐limiting for transfer. In order to determine the rate‐limiting processes, it is necessary to take a systems approach which recognises the interdependence of these processes. New technologies have the potential to deliver targeted interventions to the placenta and help poorly growing fetuses. While many factors are necessary for amino acid transfer, novel therapies need to target the rate‐limiting factors if they are going to be effective. This review will outline the factors which determine amino acid transfer and describe how they become interdependent. It will also highlight the role of computational modelling as a tool to understand this process. Abstract : Transepithelial amino acid transfer across the placenta requires interaction between different classes of amino acid transporters. Net uptake of maternal amino acids is mediated by accumulative and exchange transporters. Within the placenta amino acid levels are determined by uptake, efflux, protein synthesis and breakdown. Efflux of placental amino acids to the fetus is mediated by facilitated transporters (net efflux) and exchangers. The composition of the total amino acid pool is determined by the proportions of different amino acids in the pool; exchangers will alter the composition of the pool but not its total size.